2019
DOI: 10.15761/fnn.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accumulation of nanoparticles in soil health- a concern on future

Abstract: Nanotechnology proved as a boon to this era and is widely applied in many areas of science and technology. Agriculture is the backbone of industrial raw material and it is very important to have technologies supporting high yield, better crop production and protection in a cost effective, ecofriendly and sustainable way. Globally, there is a lot of research being conducted in the field of application of nanoparticles in agriculture. In recent time nano-based materials like nanoparticles and nanoformulations, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Most nanoparticles including magnetite enter the surroundings with no appropriate former treatment, which could lead to different effects on soil organisms [196][197][198][199][200][201][202][203]. Therefore, the authors of [204] examined the effects brought about by magnetite nanoparticles on Eudrilus eugeniae earthworm.…”
Section: Iron Oxide Nanomaterialsmentioning
confidence: 99%
“…Most nanoparticles including magnetite enter the surroundings with no appropriate former treatment, which could lead to different effects on soil organisms [196][197][198][199][200][201][202][203]. Therefore, the authors of [204] examined the effects brought about by magnetite nanoparticles on Eudrilus eugeniae earthworm.…”
Section: Iron Oxide Nanomaterialsmentioning
confidence: 99%
“…For example, ferromagnetic particles could become dislodged from biochar in soil, possibly altering soil chemistry. Although this may not have a negative effect on soil ecology (for example, Rui et al (2016) showed that maghemite nanoparticles could be used as an Fe fertiliser to improve plant growth after they were adsorbed onto the sandy soil), the use of synthetic nanoparticles in the environment is an area which should be approached with caution ( Javed et al, 2019 ). Because of this, some studies have quantified the levels of enzymatic activity and bacterial community size/composition after addition of metal oxide nanoparticles.…”
Section: Magnetic Biochar Synthesis For Ammonium Removal From Soilmentioning
confidence: 99%
“…The negative impact of silver nanoparticles disrupts plant growth and productivity but robust and smart engineered techniques are being explored for the betterment of agricultural crop production to cater to different agricultural needs. A significant increase in agricultural production could be possible through the utilization of current knowledge in the field of nanotechnology for the efficient nutrient system, good plant protection practices, efficient photo capturing system in plants, precision agriculture, and many others (Ditta et al;, Javed et al, 2019). Yet, whatever the chemical nature of nanoparticles is, one should remember potential adverse effects, i.e., phytotoxicity at high concentrations and toxicity for unintended non-target organisms.…”
Section: F Surface-enhanced Raman Spectroscopy (Sers)mentioning
confidence: 99%